CEO tenure and firm value - Francois Brochet; Peter Limbach; Markus M. Schmid; Meik Scholz-Daneshgari (University of Cologne, Centre for Financial Research (CFR), 2019)
Our study is the first to provide systematic evidence of a hump-shaped CEO tenure-firm value relation. This pattern is supported by announcement returns to sudden CEO deaths, which mitigate endogeneity concerns. Furthermore, the hump shape is subject to meaningful cross-sectional variation: firm value starts to decline after fewer years of CEO tenure i) in more dynamic industries, in which the optimal CEO-firm match changes more frequently, ii) if CEOs are less adaptable to changes, iii) if CEO entrenchment is higher. Lastly, financial reporting quality also follows a hump shape while earnings smoothing increases over CEO tenure, suggesting that CEOs entrench themselves by obfuscating their declining performance. While we find evidence suggesting optimal retention by boards on average, some CEOs stay past their “peak”, primarily because of a deteriorating CEO-firm match in conjunction with increasing entrenchment.
Keywords: G30; G34; J24; 330; CEO adaptability; corporate governance regulation; entrenchment; environmental dynamics; financial reporting quality; firm value